Inherited predisposition to endometrial cancer: Moving beyond Lynch syndrome. Issue 5 (5th November 2014) - Stadler, Zsofia K.; Robson, Mark E.
<x xml:space="preserve">Abstract</x> A number of predisposition syndromes include endometrial cancer as a component tumor. These can generally be identified on the basis of the family history and the individual phenotype.